Predictors and signatures of recovery from neglect in acute stroke. Issue 4 (15th March 2016) - Umarova, Roza M.; Nitschke, Kai; Kaller, Christoph P.; Klöppel, Stefan; Beume, Lena; Mader, Irina; Martin, Markus; Hennig, Jürgen; Weiller, Cornelius
Abstract : Objective: Spatial neglect can either spontaneously resolve or persist after stroke; the latter is associated with a poorer outcome. We aimed to investigate the neural correlates and predictors of favorable versus poor recovery from neglect in acute stroke. Methods: In addition to neuropsychological testing, we explored task‐related functional magnetic resonance imaging activation and functional connectivity in 34 patients with neglect and/or extinction. Patients were examined at 2 to 3 days (acute phase I) and 8 to 10 days (acute phase II), and some of them at 4 to 6 months (chronic phase) poststroke. Results: Course of recovery was predicted by the strength of functional connectivity between the right parietal and left prefrontal and parietal regions, as early as acute phase I. During acute phase II, favorable recovery from neglect was associated with increased activation in the left prefrontal and right parietal regions, an effect not observed at any time point in patients with poor acute recovery. The extent of neglect amelioration correlated with activation gain in the right attention centers; stronger activation of their left functional homologues correlated with better spatial processing in the neglected hemispace during both of the acute examination phases. Interpretation: System excitability and early recruitment of contralesional functional homologues represented specific features of favorable recovery in acute stroke. In severe strokes leading to neglect, contralesional functional homologues support recovery by modulating the preserved ipsilesional network, and initial functional connectivity between them might predict recovery course and help to identify patients with potentially poor recovery requiring more intensive early rehabilitation. Ann Neurol 2016;79:673–686